Theodore Roosevelt Collection : A major resource for the study of the life and times of the 26th president of the United States - Houghton Library (2021)
"The Theodore Roosevelt Collection, housed in Harvard’s Houghton and Widener libraries, is a major resource for the study of the life and times of the 26th president of the United States. The collection started as a research library opened in New York City by the Roosevelt Memorial Association in 1923. It was presented by that organization (known since 1953 as the Theodore Roosevelt Association) to Harvard University, Roosevelt's alma mater, in 1943." [self-descfription]